Proton transfer and esterification reactions in EMIMOAc-based acidic ionic liquids. Issue 30 (27th March 2017) - Tran, Anh T.; Lam, Phuoc H.; Miller, Alexandra M.; Walczyk, Dustin J.; Tomlin, Jay; Vaden, Timothy D.; Yu, Lei
Abstract : Proton transfer and esterification reactions are observed when formic acid and ionic liquid EMIMOAc are mixed. Abstract : Acetate-based ionic liquids (such as 1-ethyl-3-methylimidazolium acetate, EMIMOAc) have potential applications for CO2 absorption and electrochemical reduction, chemical separations and extractions, and Fischer esterification of alcohols, amines, and starch. Both strong and weak organic acids can be dissolved in EMIMOAc and yield interesting proton-rich acidic ionic liquid solutions. We have used GC-MS vapor pressure measurements, spectroscopic methods, calorimetry, and viscosity/conductivity measurements to investigate the properties and reactions of various acids dissolved in EMIMOAc. Unique proton transfer and esterification reactions are observed in many of these acidic solutions with carboxylic acids or sulfonic acids as solutes. Some acids react with the acetate anion to produce acetic acid, which provides a measure of acid strength in ionic liquid solvents. In addition, we observed an esterification reaction that might involve the imidazolium cation and the acetate anion to yield methyl acetate.